The European Union Economic System Reform (Economic and Political Thought, 2013)
The current financial crisis showed that the European Union economicconstruction lacks resistance to external shocks and that the macro-economicand financial policy of some Euro Zone states is very incautious.The necessary reconstruction consists in the creation of fiscal and banking unionsupported by common financial instruments. Further, deeper reforms areexpected.